2021
DOI: 10.1111/dmcn.14792
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgical procedures for children with myelomeningocele after fetal or postnatal surgery: a comparative effectiveness study

Abstract: Aim To compare the frequencies of neurosurgical procedures to treat comorbid conditions of myelomeningocele in patients who underwent fetal surgery versus postnatal surgery for closure of the placode. Method By utilizing the National Spina Bifida Patient Registry in a comparative effectiveness study, 298 fetal surgery patients were matched by birthdate (±3mo) and spina bifida clinic site with one to three postnatal surgery patients (n=648). Histories were obtained by record review on enrollment and yearly subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Worley et al compared the results of fetal ( n = 248) and postnatal ( n = 698) interventions in cohorts of children up to 12 months of age and found that fetal surgery was associated with lower incidence of CSF diversion for hydrocephalus by VP shunting or endoscopic third ventriculostomy as compared to postnatal surgery (110/239 (46) vs. 349/441 (79) respectively; IRR 0.61; CI95%; 0.53–0.71; p < 0.01). Repeat tethered cord release was necessary in 54/298 (18%) vs. 102/648 (16%) cases, respectively (IRR 1.22 (0.94–1.59); CI95% 0.13; 1.11 0.84–1.47; p. 46) [ 11 ]. Low position of the medullary cone remains the main diagnostic marker for a tethered spinal cord on prenatal imaging [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worley et al compared the results of fetal ( n = 248) and postnatal ( n = 698) interventions in cohorts of children up to 12 months of age and found that fetal surgery was associated with lower incidence of CSF diversion for hydrocephalus by VP shunting or endoscopic third ventriculostomy as compared to postnatal surgery (110/239 (46) vs. 349/441 (79) respectively; IRR 0.61; CI95%; 0.53–0.71; p < 0.01). Repeat tethered cord release was necessary in 54/298 (18%) vs. 102/648 (16%) cases, respectively (IRR 1.22 (0.94–1.59); CI95% 0.13; 1.11 0.84–1.47; p. 46) [ 11 ]. Low position of the medullary cone remains the main diagnostic marker for a tethered spinal cord on prenatal imaging [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in the neurological development in the randomized MOMS trial was limited by the occurrence of the TSC (tethered spinal cord) syndrome [ 9 ]. TSC remains a risk factor for less favorable neurological outcomes in the pre- and postnatal repair groups, regardless of the surgical approach (fetoscopic vs. open surgery) [ 10 , 11 ]. Our original technique of complete untethering of the spinal cord and the use of fetal native tissue (dura mater, spinal erectors, skin) for anatomic reconstruction reduce the risk of secondary TSC.…”
Section: Introductionmentioning
confidence: 99%
“…As such, they have scientifically validated, to an acceptable degree, the generalizability of the MOMS findings. Both these retrospective cohort studies suggest that single‐site fetal centers functioning outside of a randomized trial environment, respectively in Europe 3 and in the USA where results from independent centers were aggregated in the National Spina Bifida Patient Registry, 4 can achieve comparable short‐ and medium‐term outcomes to the MOMS trial.…”
mentioning
confidence: 98%
“…and Worley et al. have bridged this gap in knowledge by demonstrating different aspects of the effectiveness of fetal SBA surgery 3,4 . As such, they have scientifically validated, to an acceptable degree, the generalizability of the MOMS findings.…”
mentioning
confidence: 99%
“…17,18 Some reports demonstrate significant associations between social determinants of health and choice of approach. 19-22…”
mentioning
confidence: 99%